Crystal structure transformation and induction of shear banding in Polyamide 11 by surface modified Cellulose Nanocrystals. (7th April 2017) - Peng, Shane X.; Shrestha, Shikha; Youngblood, Jeffrey P.
Abstract: Polyamide 11 (PA11) nanocomposites reinforced with Cellulose Nanocrystals (CNC), dodecanoic acid surface modified CNC (CNC_d), and CNC with methyl laurate (CNC + ML) as plasticizer were fabricated. With the addition of CNC alone, tensile modulus and strength of the PA11 were improved, but the toughness decreased at high CNC concentration. Using CNCs that were surface modified, the tensile modulus and strength both increased while the toughness of PA11 was preserved. CNC_d also led to the formation of shear band like structures during uniaxial tensile testing. When PA11 and nanocomposites were annealed near their melting point, a higher Tm peak indicated that smaller crystals were melted and recrystallized. The addition of CNC inhibited this transformation, while CNC_d promoted it at early stages of annealing. Overall, the combination of shear banding and crystal transformation inducing properties of surface modified CNC provides an intriguing option for future improvement of CNC polyamide nanocomposites. Graphical abstract: Highlights: Dodecanoic acid surface modified CNC (CNC_d) induced shear banding in PA11 during tensile testing. Unmodified CNC improved modulus and strength of PA11, while CNC with methyl laurate (CNC + ML) improved elongation. CNC_d had mechanical properties that are in between unmodified CNC and CNC + ML. During annealing of PA11, CNC_d induced PA11 crystal transformation, while unmodified CNC inhibited the change.